Comparative morphology of the larvae of the palm weevils Dynamis borassi (Fabricius) and Rhynchophorus palmarum (Linnaeus) (Curculionidae: Dryophthorinae): Two major pests of peach palms in the Neotropics - Vásquez-Ordóñez, Aymer Andrés (2020)
The morphology of the larvae of Dynamis borassi (Fabricius) and Rhynchophorus palmarum (Linnaeus) was compared, described and illustrated. A complete definition of subtribe Rhynchophorina at the larval stage was elaborated, based on mature and submature larvae, and characters of the first instar larvae are provided for the first time. Diagnostic characters to distinguish the larvae of D. borassi and R. palmarum are mainly from the epipharynx and maxillae, but the abdominal terminal plate also provides differential features that can aid in the identification. The characterization of both species at the larval stage is expected to be useful in the implementation of new control strategies in palm plantations in South America. For practical reasons, a comparative table is appended in Spanish to serve as a quick diagnostic guide for species identification.